The global politics of combating nuclear terrorism : a supply-side approach - Hansell, Cristina; Potter, William C. ([S.l.] : Routledge, 2010)
The most difficult challenge for a terrorist organization seeking to build a nuclear weapon or improvised nuclear device is obtaining fissile material, either plutonium or highly enriched uranium (HEU). Experts acknowledge that obtaining HEU, uranium that has been processed to increase the proportion of the U-235 isotope to over 20%, is the most difficult challenge facing a state or non-state actor seeking to build a nuclear explosive. The large stocks of HEU in civilian use, many not adequately protected, are thus one of the greatest security risks facing the global community at present. This book contains chapters examining the various uses for this material and possible alternatives; the threat posed by this material; the economic, political and strategic obstacles to international efforts to end the use of HEU for commercial and research purposes; as well as new national and international measures that should be taken to further the elimination of HEU. This book was published as a special issue of The Nonproliferation Review .
Keywords: Nuclear disarmament--International cooperation; Nuclear nonproliferation--International cooperation